2008
DOI: 10.1182/blood-2008-05-156307
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells drive memory CD8 T-cell homeostasis via IL-15 transpresentation

Abstract: Interleukin-15 (IL-15 IntroductionThe generation and maintenance of memory CD8 T cells is regulated by multiple mechanisms that involve both early programming of memory T-cell precursors as well as a continuous supply of external signals. 1,2 Whereas the events and signals that program memory precursors are not well understood, interleukin-15 (IL-15) has clearly been shown to drive the generation and maintenance of memory CD8 T cells. 3,4 The recent evidence that IL-15 is delivered through the mechanism of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
119
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(130 citation statements)
references
References 36 publications
8
119
3
Order By: Relevance
“…These data might seem to contrast previous data showing that restricting expression of IL-15Ra to CD11c þ DCs resulted in a partial rescue of KLRG1 hi CD127 lo CD8 þ T cells. 31 However, only partial effects were observed in the prior study and we failed to observe enhancement of DCs in Bim-deficient mice during viral infection, suggesting that other cell types are important presenters of IL-15. Thus, Bim expression within DCs has little, if any, role on the magnitude or phenotype of the effector CD8 þ T-cell response to acute viral infection.…”
Section: Discussioncontrasting
confidence: 56%
“…These data might seem to contrast previous data showing that restricting expression of IL-15Ra to CD11c þ DCs resulted in a partial rescue of KLRG1 hi CD127 lo CD8 þ T cells. 31 However, only partial effects were observed in the prior study and we failed to observe enhancement of DCs in Bim-deficient mice during viral infection, suggesting that other cell types are important presenters of IL-15. Thus, Bim expression within DCs has little, if any, role on the magnitude or phenotype of the effector CD8 þ T-cell response to acute viral infection.…”
Section: Discussioncontrasting
confidence: 56%
“…Many studies have demonstrated that anti-tumor immunity and the ability to break tolerance could be enhanced by co-delivering additional immunomodulator genes, such as interleukin-2, interleukin-12, interleukin-15, CD70 and other activators, to DCs. 5,[57][58][59][60] We are currently conducting experiments to evaluate the anti-tumor immunity generated by the co-delivery of a tumor antigen and an immuomodulator using this DC-directed lentivector system.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin 15 (IL-15) is a pivotal cytokine for the activation and proliferation of cytotoxic CD8 + T cells (1)(2)(3). As opposed to other soluble cytokines that induce signals upon binding to their respective receptors, IL-15 delivery is relatively unique (4).…”
Section: Cytotoxic Cd8mentioning
confidence: 99%